Regulation of Distance Learning Courses in Brazilian Higher Education: A Critical Review of Decree No. 12,456/2025 and Ordinance No. 378/2025 - Barbosa Reis, Thais; Barbosa Reis Monteiro, Nathalie; Bertoia, Natacha; Fernanda Franceschi Klement, Claudia; Perrotta Lopes de Almeida Prado, Karen; Zago Dahmer, Alessandra; Rodrigues, Miriam; Ferdinando Passone, Eric (International Review of Research in Open and Distributed Learning, 2026)
This field note examines the recent regulatory framework for distance higher education in Brazil, analyzing the implications of Decree 12,456/2025 and Ordinance 378/2025. Through critical analysis, we assessed the alignment of these measures and their potential impacts on educational quality, accessibility, and institutional accountability. We examined the measures designed to balance the expansion of access with the assurance of quality, including mandated percentages of in-person and synchronous activities, redefined faculty roles, and restrictions on institutional sharing. While acknowledging the potential to enhance academic rigor and curb low-quality programs, the analysis highlighted significant implementation challenges. These include increased operational costs, potential impacts on tuition, and concerns that restricting teacher education to blended or in-person modalities may exacerbate teacher shortages in remote areas. The study concluded that the new framework’s ability to reduce inequalities and improve employability depends on financial support, vigilant oversight, and further research, offering a valuable case study for global debates on regulating digital higher education.